Assessing subjective and objective information literacy at upper secondary schools - an empirical study in four German-speaking countries. (1st June 2020) - Seufert, Sabine; Stanoevska-Slabeva, Katarina; Guggemos, Josef
Information literacy (IL) is a key 21st-century skill. This paper contributes to the body of knowledge by specifying the construct of IL. It defines IL and presents a seven-dimensional IL model. On this basis, two types of test instruments are evaluated: a performance test for objective IL (OIL) and a self-assessment instrument for subjective IL (SIL). Both instruments are validated by means of item response theory. We utilise a sample with N = 432 upper secondary students from German-speaking countries. Rasch scalability of the instruments is demonstrated. Reliability equals in the case of OIL for EAP/PV .84 and for WLE .88; in the case of SIL, .75 and .77, respectively. For OIL, we present a proficiency level model to ensure a criterion-based interpretation of test scores. In terms of instructional sensitivity, we provide evidence for a positive influence of students' grade and IL-related content in class on OIL. The correlation between OIL and SIL equals .52.